Linac Coherent Light Source data analysis using psana. Issue 2 (18th March 2016) - Damiani, D.; Dubrovin, M.; Gaponenko, I.; Kroeger, W.; Lane, T. J.; Mitra, A.; O'Grady, C. P.; Salnikov, A.; Sanchez-Gonzalez, A.; Schneider, D.; Yoon, C. H.
Abstract : The software used to analyze data produced at the Linac Coherent Light Source X‐ray free‐electron laser is described. Abstract : Psana ( Photon Science Analysis ) is a software package that is used to analyze data produced by the Linac Coherent Light Source X‐ray free‐electron laser at the SLAC National Accelerator Laboratory. The project began in 2011, is written primarily in C++ with some Python, and provides user interfaces in both C++ and Python. Most users use the Python interface. The same code can be run in real time while data are being taken as well as offline, executing on many nodes/cores using MPI for parallelization. It is publicly available and installable on the RHEL5/6/7 operating systems.